Қала мəртебесі: тарихы жəне қазіргі кейбір мəселелері - Байжанова, К.Т. (ҚарМУ басп., 2010)
Без изучения исторических корней явления невозможно оценить сегодняшнее положение вещей и опре- делить будущее, поэтому в данной статье рассматриваются исторические истоки развития казахстанских городов, проводится их типизация по различным основаниям, дается краткая характеристика нормативных актов, регулировавших статус города. Установлено, что статус нынешних городов и перспективы их развития соответствуют принципам исторического формирования и развития. Автором рассматриваются также основные научные методы изучения города. It is impossible to value the present day situation and define future without studying some historical cortex phenomena. Thus the given article is covering the historical roots of the development of kazakhstan city, trying to conduct the city in types on different basis. Also the short features of the normative acts that adjust the status of a city are given in this article. It is the fact that the status of present city and prospects of their development are corresponding to the principles of historical shaping and development. Some main scientific methods of the study of the city are also covered in this work.